Transvenous ablation of atrioventricular conduction with a low energy power source. Issue 5 (November 1989) - Rowland, E; Cunningham, D; Ahsan, A; Rickards, A
Abstract : A power source modified to increase voltage delivery and minimise arcing (for a given energy) was used for transvenous ablation of atrioventricular conduction to control refractory supraventricular arrhythmias in 14 patients. Twelve had atrial fibrillation or flutter, one had atrioventricular nodal reentry tachycardia, and the other had permanent junctional reentry tachycardia. Despite treatment with 5-7 (median 6) antiarrhythmic drugs symptoms had persisted in all the patients. Cathodal discharges of 0.5-39.5 J were delivered to the distal electrode (in one case in parallel with the middle electrode). In all patients shocks produced complete atrioventricular block; this was permanent in eleven (79%). Four patients required a second procedure. In one patient, only a transient atrioventricular block could be produced and catheter ablation with a conventional power source also failed. In the other two atrioventricular conduction was modified such that previously ineffective treatment produced satisfactory control of heart rate. The cumulative energy delivered to those in whom permanent complete heart block resulted ranged from 3.6 to 97.8 (mean 38.3) J with a mean of three shocks (range 1-7) delivered per patient. During follow up of 1-28 (mean 14) months 11 patients remained in complete heart block and free of arrhythmia.